(untitled) (Revista Brasileira de Computação Aplicada, 2017)
Online data deduplication aims to identify records that represent the same purpose on a continuous data flow environment. It must be able to process a range of information with high effectiveness and no delays. The purpose of this paper is to introduce a developed tool entitled Redblock, for real-time data deduplication, using a distributed platform for online processing combined with an Inverted Index. During the experimental evaluation, Redblock managed to provide good preliminary results in terms of efficiency and effectiveness in a database.